INTEGRAL VALUES OF ELECTROCARDIOGRAPHY IN SICK CHILDREN WITH PREMATURE VENTRICULAR EXCITATION (Journal of Science-Innovative Research in Uzbekistan, 2024)
Premature ventricular excitation syndrome means that the ventricular myocardium is activated by atrial impulses conducted through accessory pathways (AP) before the impulses reach the ventricles through the normal cardiac conduction system.Manifestations of PVS are rare - from 0.15 to 3.1% of the general population, including 9% of the total number of children with cardiac arrhythmias. This disease manifests itself in different forms - from constant clinical and electrophysiological manifestations in the manifest form to the absence of any subjective and objective symptoms in the latent form. The clinical significance of PVS is determined by the fact that almost 80.0% of patients sooner or later develop tachyarrhythmic attacks, both paroxysmal (i.e. transient) and chronic (constant - recurrent form) tachyarrhythmia, atrial fibrillation, atrial flutter, which under certain conditions are transformed into atrial and ventricular fibrillation, posing a threat to the patient's life.